Keyboard Practice, consisting of an Aria with diverse Variations for the Harpsichord with two manuals. - McDaid, John G. (Fantasy & Science Fiction, 2005)
Presents the short story "Keyboard Practice, Consisting of an Aria with Diverse Variations for the Harpsichord with Two Manuals," by John G. MacDaid.